REVITALISASI NILAI TATTWA DAN ETIKA HINDU DALAM PENDIDIKAN KARAKTER SISWA DI ERA DIGITAL - Oktaviani, Ni Made Ayu Dwi (Padma Sari: Jurnal Ilmu Pendidikan, 2025)
The digital era has significantly transformed the way students access information and engage in social interactions. However, this transformation also presents substantial challenges to the development of character and moral values. Phenomena such as information overload, the spread of misinformation, and the decline of face-to-face interaction have contributed to the erosion of moral resilience among younger generations. The core problem addressed in this study is how the revitalization of Tattwa values and Hindu ethics can serve as a relevant and effective foundation for character education amid the complexities of the digital age. Accordingly, the purpose of this study is to explore the revitalization of Tattwa values and Hindu ethics in shaping students’ character education within the context of digital society. This study adopts a descriptive qualitative approach utilizing literature review as the primary method for data collection. Data were gathered from a range of credible sources, including academic journals, scholarly books, conference proceedings, and relevant articles focused on character education and Hindu values. The data analysis process consisted of three main stages: data reduction to extract key information, systematic presentation of data in descriptive narrative form, and drawing conclusions through conceptual synthesis. The findings reveal that Tattwa values and Hindu ethical frameworks such as Catur Paramita, Tri Kaya Parisudha, Tri Hita Karana, and Panca Yadnya play a strategic role in fostering student character marked by integrity and spiritual awareness. The integration of these values into educational practices, particularly through contextual approaches that link Hindu teachings to digital phenomena such as cyberbullying can effectively enhance students' moral awareness and character resilience in a comprehensive manner.